Makna Pesan Komunikasi Iklan Minuman â€œSpriteâ€ dengan Pendekatan Roland Barthes - Munandar, Pramudita (Jurnal Mahardika Adiwidia, 2021)
One way to introduce a product to the wider community is through advertising. Advertising is needed to continuously inform product features and benefits, create preferences, and remind and place product brands in consumers' minds. many symbols and signs are used to convey messages In an advertising Likewise, in the Sprite advertisement "In fact Nyegerin" which does not use the person model, many symbols and signs are used to convey messages. Therefore, the researcher is interested in exploring the meaning of the message contained in the Sprite advertisement "In fact Nyegerin". The framework of thinking in this study is to interpret meaning using Roland Barthes' semiotic scheme where two stages of meaning are used, namely denotation and connotation to identify the meaning of messages from various scenes in the Sprite advertisement "Nyatanya Nyegerin". The primary data of this research is the Sprite tv advertisement video â€œNyatanya Nyegerinâ€ and the secondary data is the result of interviews with representatives from PT Coca Cola Amatil Indonesia. The main finding of this research is that the meaning of the message contained in the Sprite advertisement â€œNyatanya Nyegerinâ€ is: Sprite in reality, and not nonsense, is a drink that brings various goodness, is refreshing, purely healthy and is the drink of choice for young people. The meaning of this message is reflected either explicitly or implicitly from the symbols and signs identified in the Sprite advertisement "In fact Nyegerin". These symbols and signs, which are almost all non-human (not people/models), are very effective in building the construction of reality that the Sprite advertisement communicates